Impact of patient ancestry on heterogeneity of Sjögren’s disease - Xavier Mariette; Raphaele Seror; Gaetane Nocturne; Pascale Chretien; Maxime Beydon; Veronique Le Guern (RMD Open, 2023)
Objectives We aimed to compare disease characteristics between primary Sjögren’s syndrome (pSS) patients of African ancestry (AA) and Caucasian ancestry.Methods We conducted a retrospective, case–control study in a French national and European referral centre for pSS. All patients with pSS of AA were matched with two Caucasians patients having similar follow-up duration. We explored clinical and biological parameters associated with a cumulative EULAR Sjögren’s Syndrome Disease Activity Index (cumESSDAI ≥5) (consisting of individual clinESSDAI domain maximum throughout follow-up).Results We identified 74 patients of AA matched with 148 Caucasian. Median age at pSS diagnosis was younger in AA patients (43 years (IQR 33–51) vs 56 years (44.8–59.2), p<0.001). AA patients presented higher median titre of gammaglobulins (18.5 g/L (IQR 15–22.8) vs 13.4 g/L (9.9–16.9), p<0.001), more frequently positive for anti-SSA (88% vs 72%, p=0.007) and anti-RNP (11% vs 2.7%, p=0.023) antibodies. During the follow-up (median: 6 years (IQR 2–11)), AA patients presented more systemic complications: arthritis, myositis, interstitial lung disease, lymphadenopathy, central nervous system involvement. Median cumESSDAI score was higher in AA patients (7.5 (IQR 3.2–16.0) vs 4.0 (IQR 2.0–9.0), p=0.002). Interestingly, in multivariate analyses, factors associated with disease activity were sub-Saharan AA (OR 2.65 (95% CI 1.06 to 6.94)), rheumatoid factor (OR 2.50 (95% CI 1.28 to 4.96)) and anti-RNP positivity (OR 11.1 (95% CI 1.88 to 212)).Conclusion Patients of AA display higher disease activity with a hallmark of higher B-cell activation. Studies to investigate biological drivers behind such differences are needed.